Strategi Pelayanan Bimbingan Sosial dan Ketrampilan Berbahasa dalam Membentuk Perilaku Sosial ABK - Farida, Farida; Sophya, Ida Vera (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Strategy of Social Guidance Services and Language Skills in Shaping ABK's Social Behavior. This study aims to (1) find out the strategy of social guidance services and language skills in shaping the religious social behavior of ABK, (2) find out the obstacles faced by RBA as a mentoring institution. The method used in this research is descriptive qualitative. The research technique used is observation and interview. The collected data is then analyzed using descriptive-qualitative-analytical analysis techniques. The results of the study show (1) The strategy is carried out by arranging service schedules, fostering cooperative cooperation, monitoring progress, reporting social behavior activities according to developmental achievements, (2) Obstacles faced by RBA include busy parents, lack of patience in continuing therapy at RBA to be applied at home, carelessness in the food menu that affects ABK activities that cannot be controlled, less involvement of ABK in social activities at home and with the surrounding environment, lack of parental creativity in assisting the development of ABK's socio-religious behavior.Keywords: Social Guidance, Language Skills, Children with Special Needs